2014
DOI: 10.1371/journal.pone.0110550
|View full text |Cite
|
Sign up to set email alerts
|

Objective Determination of Optimal Number of Spectral-Domain Optical Coherence Tomographic Images of Retina to Average

Abstract: PurposeTo determine by objective methods the minimum number of spectral-domain optical coherence tomographic (SD-OCT) images to average to obtain the clearest retinal image.MethodsSD-OCT Images were obtained from 9 healthy eyes and also from a phantom eye model. The SD-OCT images were obtained by averaging 1, 5, 20, 60, and 100 B-scan images. The reflectivity (mean gray value) of the different retinal layers was evaluated in these images. The image quality was evaluated by the size of the standard deviations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…One method to compensate for these issues may be through en face image averaging, echoing the technique used to improve OCT image quality [3336]. Unlike previous applications of registration and averaging in OCTA which were largely focused on correcting for eye motion artifacts [34, 3739], our proposed method would require that a patient undergo multiple scans in a single session for offline image registration and averaging.…”
Section: Introductionmentioning
confidence: 99%
“…One method to compensate for these issues may be through en face image averaging, echoing the technique used to improve OCT image quality [3336]. Unlike previous applications of registration and averaging in OCTA which were largely focused on correcting for eye motion artifacts [34, 3739], our proposed method would require that a patient undergo multiple scans in a single session for offline image registration and averaging.…”
Section: Introductionmentioning
confidence: 99%
“…The number of network input ranged from 1 to 20. One reason of choosing 1 to 20 is the consideration of computation power, another reason is that a previous detailed comparative study has indicated that the optimal number was 20 while minimizing the examination time and maximizing the image quality [ 8 ]. Finally, the network output, namely the enhanced OCT image, was obtained by performing a weighted sum of the averaged multiple inputs and the restored feature maps after the decoding module.…”
Section: Methodsmentioning
confidence: 99%
“…With subjective scoring, image averaging has been proved to be a statistically significant benefit for assessing the external limiting membrane (ELM) and outer nuclear layer (ONL) [ 7 ]. Then a detailed comparative experiment indicates that OCT image quality improves with an increase in the number of frames averaged, and the optimal number is 20 while minimizing the examination time and maximizing the image quality [ 8 ]. However, image averaging requires multiple repeated scans at the same location while the subject is instructed to maintain steady fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum number of frames for image averaging during OCT imaging of the retina has been investigated based on objective and subjective determination of the improvement in a range of image quality parameters including image brightness, layer contrast and noise variance. Averaging 16–20 B‐scans significantly improves image quality metrics compared to a single non‐averaged image, with further increases in the number of frames for B‐scan averaging not significantly enhancing the image quality.…”
mentioning
confidence: 99%